Strain induced enhanced ferromagnetic behavior in inhomogeneous low doped La0.95Sr0.05MnO3+delta - Das, S. (2017)
We report an unusual high-temperature ferromagnetic transition in bulk single-phase nanocrystalline La0.95Sr0.05MnO3+delta, achieved through localized strain and inhomogeneous Sr-doping. Magnetization measurements show a well defined transition at 290K and a broad one at similar to 150 K. HRTEM imaging reveals the strain on the highly crystalline nanometer sized grains and Sr-doping gradients, while oxygen homogeneity at the grain interfaces is confirmed by EELS-spectra. The magnetic behavior, far from the expected bulk phase diagram, shows how local doping and strain can strongly tune the macroscopic properties of a bulk material. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793657]